Unravelling the underlying mechanism of computational thinking: The mediating role of attitudinal beliefs between personality and learning performance - Zhang, Shuhan; Wong, Gary K. W. (Journal of computer assisted learning, 2024)
Background Computational thinking (CT) has been broadly considered one of the 21st‐century competencies, and an emerging trend has been seen in integrating CT into primary education. Cumulative research was conducted to investigate the influencing factors of CT learning performance, and an ample range of factors has been identified, involving both cognitive and non‐cognitive facets. However, limited has been done in exploring the non‐cognitive factors, and even less at the primary education level. Objective To address this gap, this study bridged CT with personality in the primary school context, and more importantly, it proposed a mediator in the personality‐CT relationship that is, attitudinal beliefs, which are amenable to change, thereby allowing further support for nurturing the traits. Method Based on the Big Five model of personality, standard tests were administered to a sample of 434 primary school students (ages 8–11), and data were analysed using structural equation modelling via Mplus. To improve the robustness of the results, control variables (i.e., demographic features, coding experience) were added to the research model, and a bootstrap approach with 5000 resamples was used to examine the mediating effect. Result and Conclusion Findings demonstrated that Conscientiousness had a positive effect on CT, and attitudinal beliefs mediated the effect of Open‐mindedness (positive) and Negative Emotionality (negative) on CT. The study contributes to the literature by enriching the CT network with non‐intellectual components and unravelling the mechanism of CT regarding how disposition traits turn into learning performance. The results implicate practitioners on the importance of encouraging conscientious behaviours and nurturing positive attitudinal beliefs in CT primary education. Lay Description What is already known about this topic Personality traits can play a role in students' learning performance. The relationship between personality and computational thinking (CT) has been verified in teenage cohorts. Simply studying personalities may have limited practical implications, as these traits tend to be stable features that practitioners have little control over. What this paper adds This is the first study investigating the effect of personalities on CT performance at the primary education level. The study examined the association between conscientiousness and CT performance. This is the first study revealing the underlying mechanism of the personality‐CT relationship. The study identified the mediating role of attitudinal beliefs in the personality‐CT relationship. The implications of study findings for practitioners The study enriched the nomological network of CT in the primary context with essential non‐cognitive components. The study unravelled the underlying mechanism of the personality‐CT relationship, helping explain how personality traits turn into learning performance. The study indicated the importance of encouraging conscientious behaviours and nurturing positive attitudinal beliefs in CT primary education.